Suporte social e satisfação parental das mães e a relação com o desenvolvimento de crianças com autismo - Santana, Luiza Laroza Selarim (2024)
According to Urie Bronfenbrenner's Bioecological Perspective on Human Development, child development is influenced by biological characteristics and environmental experiences that the child undergoes, considering the individual, the process, the context, and time. When considering children with autism, their development may be more compromised and impacted by characteristics resulting from the disorder. Thus, the objectives of this study were to: (a) Describe the social support and parental satisfaction of mothers of children with autism; (b) Analyze the development of children with autism; (c) Relate social support and parental satisfaction of mothers with the development of children with autism and (d) Relate sociodemographic data with the child development of children with autism, social support and parental satisfaction of mothers. The study included 20 mothers of children with Autism Spectrum Disorder (the children ranged in age from two years and three months to five years and ten months). Data collection instruments included a semi-structured interview script, Brazil Criterion Questionnaire, Social Support Questionnaire, Parental Satisfaction Scale, and Portage Operationalized Inventory, administered remotely through Google Forms, WhatsApp, and/or Google Meet. Qualitative data obtained from the interview script were analyzed using categories established by the instrument. Data from the Brazil Criterion, Social Support Questionnaire, and Parental Satisfaction Scale were analyzed using descriptive methods, employing measures of central tendency and dispersion. Data from the Portage Operationalized Inventory were analyzed according to the instrument's norms. Spearman's correlation test (SPSS application for Windows) was used to correlate variables. As a result, it is evident that despite the difficulties, mothers were generally satisfied with their maternal roles, especially during moments of interaction between mothers and children. Regarding social support, the number of individuals identified as supportive was small, but satisfaction with the support received was high. Concerning the development of children with Autism Spectrum Disorder, language and socialization were the most deficient areas for children with autism. Regarding correlations, both questions related to parental satisfaction and social support showed positive and negative correlations with areas of child development. However, the majority indicated that higher parental satisfaction or satisfaction with the support received correlated with better child development. Additionally, a higher level of support was associated with greater deficits in development and a younger age of diagnosis. The support services most received by children are speech therapy, occupational therapy, and psychology. Families expressed the need for psychology for parents in the health field and psychopedagogy for children in the education field. Therefore, the development of children with autism influences parental satisfaction and vice versa, as does the social support received by the family and support services, indicating that interventions with parents with the objective of promoting more social support and parental satisfaction to them, can bring positive impacts on some aspects of child development.